High-entropy alloys - Murty, B. S.; Yeh, J. W.; Ranganathan, S. (Butterworth-Heinemann, 2014)
This book provides a complete review of the current state of the art in the field of high entropy alloys (HEA). The conventional approach to alloy design is to select one principal element and add elements to it in minor quantities in order to improve the properties. In 2004, Professor J.W. Yeh and his group first reported a new approach to alloy design, which involved mixing elements in equiatomic or near-equiatomic proportions, to form multi-component alloys with no single principal element. These alloys are expected to have high configurational entropy and hence were termed as "high entropy alloys."